SOME THEORETICAL ASPECTS OF ’DOING NOTHING’ AND DERIVATIVE REFLECTIONS FROM IT - da Silva Filho, Estanislau Alves; Martins, Raonna Caroline Ronchi; Rosa, Miriam Debieux; Estevão, Ivan Ramos (ARACÊ, 2025)
This work is dedicated to an investigation of theoretical elements related to social action, from a psychoanalytic perspective. While initially presenting a concise reflection based on a thesis about "doing nothing," it returns in a second phase to explore a consequent development of this "doing nothing," unfolding through a conceptualization of social fabric and its components. This "doing nothing" is linked, implicitly, much more to a non-acting in a protocol-driven, utilitarian, and debilitating way, affected both by the reflections of Walter Benjamin, who pointed the finger at us all saying, "You work for fascism!" – as Agamben would later ask, "How can we avoid working?" – and by the inescapable "creative idleness" of Domenico de Masi, a critic of the idolatry of work that ignores freedoms and subjectivities. We are interested in allusively highlighting such content, but objectively demonstrating the importance and power of coexistence and free time, which are indeed effective remedies against civilizational ills – although here we are thinking of clinical-political interventions in territories, that is, in care practices in services with people in situations of social vulnerability. Fighting for human rights.